Diversity, Equity, Inclusion, and Belonging in Cardiovascular Disease Fellowship Training - Ingabire Grace Balinda; Nosheen Reza (Methodist DeBakey Cardiovascular Journal)
Diversity in the healthcare workforce enhances access to care, reduces health disparities, and improves quality of care for underserved populations. Yet there is a paucity of women and underrepresented minority physicians in cardiology training programs, and progress toward achieving a diverse cardiology workforce has been slow. Here we review the merits of diversity in health care, the current landscape of the cardiology workforce, barriers to increasing the proportion of women and underrepresented minority cardiologists, and specific strategies that have been proposed to sustain and enhance diversity in cardiology training programs. Editor's Note: View a video interview with Dr. Reza discussing key concepts in her article: https://youtu.be/duS4heXXlm8